2019
DOI: 10.18870/hlrc.v9i1.436
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Distance, Acculturative Stress, Functional Social Support, and Psychological Adaptation of International Students

Abstract: This study examined how cultural distance, acculturative stress, and social support interacted to influence emotional responses among international students studying in the northern part of Cyprus. Acculturation models and the stress-buffering hypothesis served as theoretical frameworks. The research questions involved understanding whether international students experienced more negative emotional responses compared to students from the home culture and whether social support moderated acculturative stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…Previous research has shown that foreign students or international students who have difficulty in adjusting experience anxiety and may suffer from depression [ 18 , 19 ]. This is consistent with the findings of a literature review, that foreign students experience problems related to their adjustment [ 46 ]. It can be an important consideration in the literature review used here that social support has a contribution to reducing acculturative stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous research has shown that foreign students or international students who have difficulty in adjusting experience anxiety and may suffer from depression [ 18 , 19 ]. This is consistent with the findings of a literature review, that foreign students experience problems related to their adjustment [ 46 ]. It can be an important consideration in the literature review used here that social support has a contribution to reducing acculturative stress.…”
Section: Discussionsupporting
confidence: 92%
“…This can be seen from the study by [ 48 ], which was conducted in Asian countries, which found that acculturative stress was negatively related to social support in a sample of international students who were studying in Malaysia. [ 52 ] Found similar results, that social support is negatively correlated with acculturative stress in international students in Korea, which was similar to the results of research conducted in the United States [ 35 , 46 , 47 , 49 , 50 , 51 ]. The largest contribution value ( r ) was found in the study of [ 48 ], within the context of Malaysian culture.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This hypothesis states that the degree to which the home and the host environment are perceived to differ will affect students’ adjustment: more perceived differences will go together with more difficulties to adjust. However, there are also a considerable number of studies reporting no significant relationship between CD and adjustment of international students (Bastien et al, 2018; Cetinkaya-Yildiz et al, 2011; Ladum and Burkholder, 2019; Selmer and Lauring, 2009); therefore, we suggest that the relationship between the two constructs may have been influenced by another factor.…”
Section: Cultural Distance As a Predictor Of International Students’ ...mentioning
confidence: 73%
“…Cluster 5 focuses on international students' acculturative challenges and mental health as they study abroad. Multicultural experts have observed that studying in a foreign country presents challenges, including language barriers (e.g., Yu & Shen, 2012), culture shock (e.g., Presbitero, 2016), cultural distance (e.g., Ladum & Burkholder, 2019), discrimination (e.g., J. J. Lee & Rice, 2007), and racism (e.g., Rojas et al, 2021).…”
Section: Most Prolific Authorsmentioning
confidence: 99%